Lifestyle Moderates Fintech Peer to Peer Lending and Risk Talking which Impact on Consumer Behavior - Munazat, Mumu; Dasmaran, Verliani; Sutihat, Eva (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to analyze and prove the influence of fintech peer to peer lending and Risk Taking Behavior on Consumptive Behavior moderated by Lifestyle in Adolescents in Pandeglang Regency. This type of research is quantitative using primary data measured by a Likert scale. The number of samples used in this study was 400 adolescent respondents aged 15-24 years in the Pandeglang Regency area. This study uses the PLS-SEM analysis method which is processed with the smartPLS 4.0 program. The results of this study indicate that fintech peer to peer lending has a significant effect on consumptive behavior, Risk taking behavior has a significant effect on consumptive behavior, Lifestyle is able to moderate the relationship between fintech peer to peer lending and consumptive behavior, Lifestyle is able to moderate the relationship between risk taking behavior and consumptive behavior.